2005
DOI: 10.1182/blood-2005-03-0918
|View full text |Cite
|
Sign up to set email alerts
|

Altered NKG2D function in NK cells induced by chronic exposure to NKG2D ligand–expressing tumor cells

Abstract: NKG2D is an activation receptor that allows natural killer (NK) cells to detect diseased host cells. The engagement of NKG2D with corresponding ligand results in surface modulation of the receptor and reduced function upon subsequent receptor engagement. However, it is not clear whether in addition to modulation the NKG2D receptor complex and/or its signaling capacity is preserved. We show here that the prolonged encounter with tumor cell-bound, but not soluble, ligand can completely uncouple the NKG2D recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
223
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(231 citation statements)
references
References 32 publications
6
223
1
Order By: Relevance
“…4D). In mice expressing transgenic human NKG2D-L or harboring NKG2D-Lexpressing tumor cells, NKG2D down-regulation was also observed [40][41][42].…”
Section: Discussionmentioning
confidence: 95%
“…4D). In mice expressing transgenic human NKG2D-L or harboring NKG2D-Lexpressing tumor cells, NKG2D down-regulation was also observed [40][41][42].…”
Section: Discussionmentioning
confidence: 95%
“…100 Importantly, this strategy must be examined with scrutiny because sustained exposure of NKG2D ligands, either membrane-bound or in soluble form, to their receptor results in reduced NKG2D expression and impaired NK cell killing capacity. [102][103][104] Finally, several cytokines (for example, IFN-a, IL-15, TGF-b) were demonstrated to affect NKG2D ligand expression, but have not been tested on AML cells. 4,84 The proteasome inhibitor bortezomib and the histone deacetylase inhibitor depsipeptide were also shown to improve NK-cellmediated killing of AML cells through the death-receptor pathway TNF-related apoptosis-inducing ligand (TRAIL).…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…20,21 Thus, it is possible that sustained engagement of NKG2D by iMICA protein might decrease the expression of NKG2D on the surface of NK cells. However, we found that the expression of NKG2D in NK cells activated for 1 week did not decrease when compared with freshly isolated NK cells (Figure 1e).…”
Section: Mica Synergizes With Ilmentioning
confidence: 99%